2010
DOI: 10.1371/journal.pone.0010778
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Mitochondrial Homeostasis in the Skeletal Muscle of Sedentary Older Adults

Abstract: The role of mitochondrial dysfunction and oxidative stress has been extensively characterized in the aetiology of sarcopenia (aging-associated loss of muscle mass) and muscle wasting as a result of muscle disuse. What remains less clear is whether the decline in skeletal muscle mitochondrial oxidative capacity is purely a function of the aging process or if the sedentary lifestyle of older adult subjects has confounded previous reports. The objective of the present study was to investigate if a recreationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
175
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(185 citation statements)
references
References 90 publications
(111 reference statements)
10
175
0
Order By: Relevance
“…In contrast to previously reported mitochondrial dysfunction in elderly [28,39,53], the present findings are in line with previous studies showing that mitochondria from skeletal muscle of elderly subjects are well functioning [44,47]. The finding that both the endurance trained and untrained elderly subjects in the present study had ~2 fold lower αKG-DH/CS activity ratio than previously observed in young subjects [2], is apparently due to a higher CS activity rather than a…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to previously reported mitochondrial dysfunction in elderly [28,39,53], the present findings are in line with previous studies showing that mitochondria from skeletal muscle of elderly subjects are well functioning [44,47]. The finding that both the endurance trained and untrained elderly subjects in the present study had ~2 fold lower αKG-DH/CS activity ratio than previously observed in young subjects [2], is apparently due to a higher CS activity rather than a…”
Section: Discussionsupporting
confidence: 87%
“…However little is known about the ability to prevent the potential age-associated decrease in oxidative enzyme capacity with exercise training, although previous observations indicate that this might be possible [47]. Thus, previous studies reported that elderly orienteer runners had SDH, CS and 3-hydroxy-acyl-CoA-dehydrogenase (HAD) activities at the same level as endurance trained young subjects [9,48].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial abnormalities and mtDNA mutagenesis are well-established intrinsic instigators that drive multisystem degeneration, stress intolerance, and energy deficits during aging in humans (3), monkeys (4), and rodents (5). Reduced mitochondrial quality and content in multiple tissues is also implicated in several aging-associated conditions, including cancer, obesity, cardiovascular diseases, hypertension, type 2 diabetes, osteoporosis, and dementia, as well as in the pathogenesis of neurometabolic syndromes, psychiatric disorders, end-stage renal disease, and mitochondrial cytopathies (6)(7)(8)(9)(10). Current treatment strategies for conditions associated with mitochondrial dysfunction address the secondary symptoms but not the deficiency itself (11).…”
mentioning
confidence: 99%
“…From a functional perspective, the study of the regulation of mitochondrial biogenesis has obvious implications for both human health and performance. Impaired mitochondrial function is associated with the pathology of many metabolic disorders such as insulin resistance and type 2 diabetes [2], obesity [3], ageing [4] and cancer [5]. In relation to exercise performance, the increased mitochondrial content that accompanies exercise training ensures that exercise in the trained state induces less disturbance to metabolic homeostasis for a given exercise intensity.…”
mentioning
confidence: 99%